2003
DOI: 10.1124/jpet.103.048702
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic Glutamate Subtype 5 Receptors Modulate Locomotor Activity and Sensorimotor Gating in Rodents

Abstract: Use-dependent N-methyl-D-aspartate receptor (NMDAR) antagonists produce behaviors in human volunteers that resemble schizophrenia and exacerbate those behaviors in schizophrenic patients, suggesting that hypofunction of NMDAR-mediated neuronal circuitry may be involved in the etiology of clinical schizophrenia. Activation of the metabotropic glutamate receptor subtype 5 (mGluR5) enhances NMDAR-mediated currents in vitro. Thus, activation of mGluR5 could potentiate hypofunctional NMDARs in neuronal circuitry re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
154
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 206 publications
(169 citation statements)
references
References 49 publications
(46 reference statements)
13
154
1
1
Order By: Relevance
“…Our results confirmed previous findings showing that mGluR5 À/À mice have a PPI deficit (Henry et al, 1999;Brody et al, 2004a, b;Kinney et al, 2003) that could not be impaired further by MK-801. We go on to show that the PPI deficit of mGluR5 À/À mutants was completely restored by CX546 facilitated LI in control C57BL/6J mice under conditions, which parametrically disrupted LI, when given only in the conditioning session.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results confirmed previous findings showing that mGluR5 À/À mice have a PPI deficit (Henry et al, 1999;Brody et al, 2004a, b;Kinney et al, 2003) that could not be impaired further by MK-801. We go on to show that the PPI deficit of mGluR5 À/À mutants was completely restored by CX546 facilitated LI in control C57BL/6J mice under conditions, which parametrically disrupted LI, when given only in the conditioning session.…”
Section: Discussionsupporting
confidence: 93%
“…A functional interactions between mGluR5 and NMDAR is well supported by the literature (Salter and Kalia, 2004) and our own data (Jia et al, 1998;Huang et al, 2001;Hannan et al, 2001). Indeed, several observations have shown that agonists and antagonists of mGluR5 may, respectively, attenuate and potentiate the effects of NMDAR antagonists in vivo (Kozela et al, 2003;Kinney et al, 2003;Homayoun et al, 2004). As mGluR5 antagonist administered alone could not disrupt PPI, but could enhance the effects of PCP (Kinney et al, 2003), it is possible that the PPI deficit in mGluR5 mutants might result from an interaction between NMDAR hypofunction together with missing mGluR5 complex rather than the alternative of only a parallel pathway downstream of mGluR5.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations